PENANGGULANGAN TINDAK PIDANA TERORISME ANTARA INDONESIA DENGAN IRAK - Abdillah Adi Wiranata Kusuma; Ilham Aji Pangestu; Muhammad Rizqi Fadhlillah; Dian Yulviani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
This research aims to analyze the comparison of counter-terrorism policies between Indonesia and Iraq. This research is a descriptive normative legal research. Legal materials consist of primary and secondary legal materials obtained through literature study. The approaches used include legislative approach, conceptual approach and case approach. Based on the results of the research, it is known that the differences in counterterrorism between Indonesia and Iraq lie in the security context, regulations and institutions that handle acts of terrorism. The similarities include using intelligence approach, prioritizing national security, and the existence of counterterrorism agency. As for the researcher's suggestions, first, strengthen the authority of the National Counterterrorism Agency (BNPT). Second, revise the rules related to the State Institutions that handle Terrorism, and strengthen efforts in preventing terrorism in the wider community, regarding radicalism, extremism, which threatens the stability of the State.Keywords: terrorism, crime, countermeasures. Keywords: terrorism; crime; countermeasures;